BINOL‐Fused Maleimides – A New Class of C2‐Symmetric Chiral Imides. Issue 6 (24th January 2013) - Brenet, Simon; Baptiste, Benoit; Philouze, Christian; Berthiol, Florian; Einhorn, Jacques
Abstract: The first synthesis of BINOL‐fused maleimides has been developed. This new chiral scaffold is easily accessible from various BINOL analogues and 2, 3‐dihalomaleimide derivatives under basic conditions. It can be easily functionalized on the BINOL moiety and is an entry towards promising new classes of chiral organocatalysts and ligands. Abstract : The first synthesis of BINOL‐fused maleimides has been achieved. This type of new chiral scaffold can be easily obtained from various BINOL analogues and 2, 3‐dihalomaleimide derivatives under basic conditions and can be easily functionalized on the BINOL moiety. BINOL‐fused maleimides are promising new classes of chiral organocatalysts and ligands.